Reducing maternal mortality on a countrywide scale: The role of emergency obstetric training. Issue 8 (November 2015) - Moran, Neil F.; Naidoo, Mergan; Moodley, Jagidesa
Abstract : Training programmes to improve health worker skills in managing obstetric emergencies have been introduced in various countries with the aim of reducing maternal mortality through these interventions. In South Africa, based on an ongoing confidential enquiry system started in 1997, detailed information about maternal deaths is published in the form of regular 'Saving Mothers' reports. This article tracks the recommendations made in successive Saving Mothers reports with regard to emergency obstetric training, and it assesses the impact of these recommendations on reducing maternal mortality. Since 2009, South Africa has had its own training package, Essential Steps in the Management of Obstetric Emergencies (ESMOE), which the last three Saving Mothers reports have specifically recommended for all doctors and midwives working in maternity units. A special emphasis has been placed on the need for the simulation training component of ESMOE, also called obstetric 'fire drills', to be integrated into the clinical routines of all maternity units. The latest Saving Mothers report (2011–2013) suggests there has been little progress so far in improving emergency obstetric skills, indicating a need for further scale-up of ESMOE training in the country. The example of the KwaZulu-Natal province of South Africa is used to illustrate the process of scale-up and factors likely to facilitate that scale-up, including the introduction of ESMOE into the undergraduate medical training curriculum. Additional factors in the health system that are required to convert improved skills levels into improved quality of care and a reduction in maternal mortality are discussed. These include intelligent government health policies, formulated with input from clinical experts; strong clinical leadership to ensure that doctors and nurses apply the skills they have learnt appropriately, and work professionally and ethically; and a culture of clinical governance.